2016
DOI: 10.1037/xge0000167
|View full text |Cite
|
Sign up to set email alerts
|

Followers are not followed: Observed group interactions modulate subsequent social attention.

Abstract: We asked whether previous observations of group interactions modulate subsequent social attention episodes. Participants first completed a learning phase with 2 conditions. In the "leader" condition 1 of 3 identities turned her gaze first, followed by the 2 other faces. In the "follower" condition, 1 of the identities turned her gaze after the 2 other faces had first shifted their gaze. Thus, participants observed that some individuals were consistently leaders and others followers of others' attention. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 27 publications
(39 reference statements)
4
39
0
Order By: Relevance
“…Consistent with these results, studies have also reported greater gaze following for gaze cues displayed by high‐status individuals, relative to gaze cues displayed by low‐status individuals, using a wide array of social status manipulations, including physical dominance, professional prestige, political leadership, and leadership inferred from group dynamics . As outlined before, Jones and colleagues reported greater gaze following for dominant‐looking faces relative to nondominant faces .…”
Section: The Three Core Processessupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with these results, studies have also reported greater gaze following for gaze cues displayed by high‐status individuals, relative to gaze cues displayed by low‐status individuals, using a wide array of social status manipulations, including physical dominance, professional prestige, political leadership, and leadership inferred from group dynamics . As outlined before, Jones and colleagues reported greater gaze following for dominant‐looking faces relative to nondominant faces .…”
Section: The Three Core Processessupporting
confidence: 66%
“…Finally, Capozzi and colleagues used an adapted gaze–cuing procedure involving multiple faces, in which some individuals emerged as group leaders (i.e., they turned their gaze first and the other faces followed their gaze) and others as group followers (i.e., always following others' gazes). When participants were later presented with a gaze‐cuing task, in which either images of leaders’ or followers’ gazes served as cuing stimuli, they exhibited greater gaze following in response to gaze cues displayed by leaders relative to gaze cues displayed by followers . Together, these studies show that social attention depends on evaluative processes that act to prioritize social cues coming from certain agents over others based on their social status.…”
Section: The Three Core Processesmentioning
confidence: 79%
“…The current results can be supported by previous studies at the individual level. In previous gaze cue studies, cueing strength was found to be modulated by social status (Dalmaso, Galfano, Coricelli, & Castelli, 2014;Dalmaso, Pavan, Castelli, & Galfano, 2012), political temperament (Carraro, Dalmaso, Castelli, & Galfano, 2015;Liuzza et al, 2011), facial expression (Lassalle & Itier, 2013;Tipples, 2006), facial dominance (Jones et al, 2010), and even social interaction history (Capozzi, Becchio, Willemse, & Bayliss, 2016;Dalmaso, Edwards, & Bayliss, 2016). Take, for example, social status.…”
Section: Discussionmentioning
confidence: 98%
“…This is especially true for humans, where high-status individuals can provide guidance, protection and knowledge to subordinates [2,29,30]. Indeed, human adults [31][32][33], human toddlers [34], and adult bonobos [35] prefer high-status individuals to low-status ones. Here we present 6 experiments testing whether 10-to 16-monthold human infants choose high-or low-status individuals-specifically, winners or yielders in zero-sum conflicts-and find that infants choose puppets who yield.…”
Section: Discussionmentioning
confidence: 99%